THE RECONSTRUCTION OF RAILWAYS DURING THE CRISIS SITUATIONS - Olefirenko, S. I.; Yakovliev, S. O.; Bychkov, V. V.; Kozinsk, V. A. (Science and Transport Progress, 2007)
The article studies interconection of the types of destruction of permanent way and artificial buildings and the methods of their restoration by the subdivisions of Special Governmental Transport Service and proves the importance of timely creation of necessary reserves of restorative means and facilities, constructions, capacities and equipment for efficient restoration of railways in crisis-like situations.